Segmenting Hotel Guests: The Case of Five Star Hotels in Langkawi (Malaysian Management Journal, 1999)
Segmentation is a very important element in the overall process of target marketing for tourism products as it assists in obtaining information on the segments of tourist that exist in the population served. Knowing the segments is imperative to help decide the type and amount of resources that should be allocated to target the desired segments. This study segmented five star hotel guests in Langkawi using sociodemography and psychography as segmentation bases. Applying Ward's Minimum Variance Method as the clustering technique, the findings of this research indicated that there are three categories of tourists that the participating hotels need to consider when designing their marketing strategies. The three clusters were the Fun and Excitement Holiday Seeker, the Active Weekend Holiday Seeker, and the Quiet and Meaningful Elitist Holiday Seeker: The characteristics of each cluster were described and a comparison of sociodemographic characteristics across clusters was made. Suggestions on how to best target each identified cluster were also provided.